Gestión administrativa aplicada a la Comercializadora de Fertilizantes “Jenedyd Giraldo” en la ciudad de Babahoyo, periodo 2023. - Narváez García, Mauro Bladimir (2024)
The case study, which is presented below, is based on an analysis of the administrative management applied to the fertilizer marketing company "JENEDYD GIRALDO" in the city of Babahoyo, in which the causes of the absence of the administrative process within the stages were analyzed: planning, organization, direction and control; In the same way, the negative impacts that the company sustained in the 2023 period due to the lack of organization were examined. Prejudicial elements were recorded during the investigation process, from divided opinions on internal communication in the company, to the need to integrate management tools within administrative areas. Within the implemented method, the collaborators and the owner manager were taken into account because they are employees of the organization, as well as research techniques were applied for the respective data collection, in this way satisfying the needs of the project. It was concluded that the company must take action on the matter, due to the latent threat in the company, since the deficiency lies in the disorganization, where it is essential to execute administrative processes in each operation carried out as a marketing effect.